2020
DOI: 10.1109/access.2020.2991930
|View full text |Cite
|
Sign up to set email alerts
|

A Lane Tracking Method Based on Progressive Probabilistic Hough Transform

Abstract: Lane departure warning systems have gained considerable research interest in the past decade for its promising usage in automotive, where lane detection and tracking is applied. However, it is a challenging task to improve the robustness of lane detection due to environmental factors, such as perspective effect, possible low visibility of lanes, and partial occlusions. To deal with these issues, we propose a reliable vision-based real-time lane markings detection and tracking system that can adapt to various e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 52 publications
(117 reference statements)
0
29
0
Order By: Relevance
“…Fourth, it is capable of detecting nearby structures to map robust relevant landmarks for highspeed railway mapping [18]. Lastly, it can be used to detect and track road lanes for lane departure warning systems [19].…”
Section: A Line-based Methodsmentioning
confidence: 99%
“…Fourth, it is capable of detecting nearby structures to map robust relevant landmarks for highspeed railway mapping [18]. Lastly, it can be used to detect and track road lanes for lane departure warning systems [19].…”
Section: A Line-based Methodsmentioning
confidence: 99%
“…Duan et al 39 even applied a trapezoid region as ROI, as shown in Figure 9(a). Considering a fixed size of ROI may not be appropriate for all conditions; both Wu et al 40 and Marzougui et al 41 employed an adaptive ROI approach. Similarly, with restrictions in the r-c plane, some studies limited the polar angle range in Hough space.…”
Section: Optimization Directionsmentioning
confidence: 99%
“…Again, such a range was also chosen personally based on their specific images. Zhou and Chen 43 argued the left boundary to be between [20 , 75 ] and the right one to be located in the range of [105 , 165 ], while Marzougui et al 41 chose [15 , 70 ] and [110 , 165 ] as the corresponding interest ranges. In the authors' viewpoint, the search range depends on vehicle pose and mounting location of cameras, and thus, various choices of the search range are reported.…”
Section: Optimization Directionsmentioning
confidence: 99%
“…The length estimation method adopts the Probabilistic Hough Transform method [29]. The standard Hough Transform essentially maps the image to its parameter space.…”
Section: Length Estimationmentioning
confidence: 99%